A Study on the Adjustment of Emulsification Degree to Interlayer Interference in Class III Reservoir - Bin Huang; Tingge Dai; Hongjuan Liu; Cheng Fu; Tingting Zhu; Wei Zhang (International Journal of Polymer Science)
Emulsions play an important role in enhancing oil recovery during the reservoir flooding process. In order to reveal the profile control ability and the effect of adjustments to the interlayer interference during the migration of the emulsion in the porous media, a stable emulsion system and an alkali-surfactant-polymer (ASP) system were selected to simulate the underground emulsification process by verifying influencing factors of the emulsion. A parallel-core displacement experiment was used to investigate the oil displacement efficiency and the difference of fractional flow in each layer under different emulsification degrees and different permeability contrasts. The results indicate that the stability of the emulsion is related to the shearing strength, the water content, and the type and concentration of chemical system. The oil displacement efficiency of emulsion flooding is better than that of ASP flooding. For parallel core with an average permeability of 40 mD and a permeability contrast of 2, the emulsion flooding can enhance oil recovery by 21.16% compared to water flooding. With increasing permeability contrast, the oil recovery percent of emulsion flooding will further increase. The emulsion system has good profile control ability. Within a certain range, the stronger the heterogeneity of porous media, the better the effect of emulsification on the adjustment of the interlayer interference.